2018
DOI: 10.1097/iae.0000000000001697
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical and Structural Progression With Visual Acuity Loss in Macular Telangiectasia Type 2

Abstract: Ellipsoid zone loss is frequently found in macular telangiectasia Type 2 and is an important structural component reflecting visual function. Its presence in the fovea significantly correlates with worse visual prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 23 publications
5
46
0
Order By: Relevance
“…In the present study, the eyes with ELM, EZ, and IDZ disruptions, indicating photoreceptor damage, had worse visual acuity regardless of the foveal centre involvement. This is in accordance with the longitudinal study by Peto et al 10 . They reported that the clinically meaningful loss of visual acuity occurred as the EZ disruption progresses to the foveal centre although a statistically significant modest loss of the mean vision was observed in the presence of EZ disruption on OCT 10 .…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the eyes with ELM, EZ, and IDZ disruptions, indicating photoreceptor damage, had worse visual acuity regardless of the foveal centre involvement. This is in accordance with the longitudinal study by Peto et al 10 . They reported that the clinically meaningful loss of visual acuity occurred as the EZ disruption progresses to the foveal centre although a statistically significant modest loss of the mean vision was observed in the presence of EZ disruption on OCT 10 .…”
Section: Discussionsupporting
confidence: 94%
“…The latter event directly affects central vision as the fovea is involved (Peto et al. ). Both events are possible to document reliably using OCT imaging – an objective, structural method.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible major event in MacTel is the incidence of subretinal neovascular proliferation (SRNV) (Peto et al. ). This appears to be a secondary complication of the disease and may occur at any point during the evolution of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 In general, VA decreases at a very slow rate of approximately 1 letter per year. 17 However, although VA may test well in patients with MacTel, visionrelated quality of life is reduced compared with patients with early age-related macular degeneration (AMD) and similar VA. 18 Funduscopic features present in eyes in the Mac-Tel Project cohort at baseline, as graded on color fundus photographs, included a loss of retinal clarity / grayish perifoveal sheen (74%), telangiectatic macular vessels (51%), retinal pigment epithelial (RPE) hypertrophy (33%), blunted "right-angle" venules (29%), and crystalline deposits (21%) ( Figures 1A and 2A). 9 There are no peripheral retinal abnormalities in MacTel.…”
Section: Clinical Featuresmentioning
confidence: 99%